The Impact Of Administrative Development Indicators In Improving Health Sector Performance (A Field Study On Public Hospitals In Damascus Governorate) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The study aimed to test the impact of administrative development indicators on improving the performance of the health sector by conducting a field study on public hospitals in Syria, specifically in the Damascus governorate, where the administrative development indicators issued by the Ministry of Administrative Development were approved (institutional organization quality, simplifying procedures, combating corruption and responding to complaints, citizen satisfaction, employee satisfaction) as an independent variable, And improving the performance of the health sector as a dependent variable.The study relied on the quantitative approach in both its descriptive and analytical methods. The study sample consisted of 400 individuals, the questionnaire was distributed to them, and 384 valid questionnaires were retrieved. The data were analyzed and hypotheses tested using the SPSS program.The study found results: There is an effect for all indicators of administrative development (institutional organization quality, simplification of procedures, combating corruption and responding to complaints, employee satisfaction, citizen satisfaction) in improving the performance of the health sector in public hospitals in the governorate of Damascus, which is the subject of the study.